Nilotinib and peginterferon alfa-2a for newly diagnosed chronic-phase chronic myeloid leukaemia (NiloPeg): a multicentre, non-randomised, open-label phase 2 study. Issue 1 (January 2015) - Nicolini, Franck E; Etienne, Gabriel; Dubruille, Viviane; Roy, Lydia; Huguet, Françoise; Legros, Laurence; Giraudier, Stéphane; Coiteux, Valérie; Guerci-Bresler, Agnès; Lenain, Pascal; Cony-Makhoul, Pascale; Gardembas, Martine; et al.
Summary: Background: Nilotinib is now recommended for patients with newly diagnosed chronic myeloid leukaemia in chronic phase and leads to important rates of molecular response 4·5 log (MR 4·5 ), allowing the prospect of therapy cessation. However, most patients do not reach this criterion and nilotinib is taken for lengthy periods, resulting in chronic or late-onset adverse events. Nilotinib combined with interferon might further increase rates of MR 4·5, avoid late side-effects, and allow therapy cessation. In a phase 2 trial we aimed to assess the feasibility, safety, and deep molecular response of the combination of nilotinib (600 mg daily) and peginterferon alfa-2a in newly diagnosed patients with chronic-phase chronic myeloid leukaemia (CML). Methods: In a non-randomised, open-label, phase 2 trial, we enrolled adult patients (age ≥18 years) without any organ failure who had BCR-ABL-positive, chronic-phase CML, at diagnosis. After a priming procedure with 90 μg per week of peginterferon alfa-2a alone for a month, we gave patients peginterferon alfa-2a 45 μg per week combined with nilotinib 600 mg daily until 24 months after interferon initiation. The primary endpoint was the cumulative incidence of MR 4·5 at 12 months after initiation of peginterferon alfa-2a. Data were analysed by a modified intention-to-treat principle. This trial is registered at the European Clinical Trials Database (EudraCT), number 2010-019786-28. Findings: Between March 24, 2011, and Sept 27, 2011, we enrolled 42 patients. One patient withdrew consent before receiving any study treatment so was excluded from analysis; 41 patients received treatment with peginterferon alfa-2a and nilotinib. At 12 months, seven (17%) patients had achieved MR 4·5 . Haematological and hepatic adverse events were frequent—with grade 3–4 neutropenias occurring in ten (24%) patients, grade 3–4 thrombocytopenias occurring in ten (24%) patients, grade 3–4 cholestatic events occurring in seven (17%) patients, and grade 3–4 elevations in aspartate aminotransferase or alanine aminotransferase occurring in three (7% patients—particularly during the first 3 months. However, 30 (73%) patients remained on interferon therapy at 1 year. Three grade 3–4 cardiac events (7% of patients, all coronary stenoses) occurred at later timepoints. Interpretation: The combination of peginterferon alfa-2a resulted in good molecular responses in patients. Despite substantial toxic effects, most patients remained on the study drugs for more than a year. This combination should now be tested in a randomised controlled trial. Funding: Novartis Pharma.